Voluntary sector HRM: Examining the influence of Government - Kelliher, Clare; Parry, Emma (Emerald Group Publishing Limited, 2011)
Purpose - This paper seeks to examine the practice of human resource management (HRM) in the UK voluntary sector. In recent years many voluntary sector organisations have experienced a changing context, where they have become increasingly involved in contracting for the provision of publicly funded services. This paper examines the suggestion made by a number of commentators that as a result the government has exercised influence over the way in which human resources are managed in this sector. Design/methodology/approach - The paper uses data from the Workplace Employment Relations Survey 2004 (WERS 2004) to examine HRM practice in the voluntary sector and compares this with the public and private sectors. Findings - The findings show that most voluntary sector organisations have adopted performance-oriented HR practices, communication and involvement schemes, and welfare-oriented practices. This suggests a departure from the relatively unsophisticated HRM that has traditionally been found in the voluntary sector and which may be as a result of the influence of government on HRM standards in the sector. Research limitations/implications - Future research, which adopts a longitudinal approach, would allow the impact of government influence on HRM practices in the voluntary sector to be examined in more depth. Originality/value - This paper represents a rare examination of HRM practice across a wide range of voluntary sector organisations and provides insight into the potential influence of government on HRM in the sector.